The JBI Transfer Science Scholarly Framework. Issue 4 (December 2016) - Stern, C.; Munn, Z.; Porritt, K.
Abstract : Background: The mission of the Joanna Briggs Institute (JBI) is to synthesize, transfer and facilitate the implementation of the best available evidence related to the feasibility, appropriateness, meaningfulness and effectiveness of health policy and practice. The transfer of evidence into direct clinical practice is a complex and challenging component of evidence-based healthcare that has yet to be mastered. Objective: To introduce the JBI Transfer Science Scholarly Framework which outlines priority areas for investigation and research related to the field of transfer science. Methods: The JBI Transfer Science Scholarly Framework sits within and is aligned to the JBI Scholarly Framework. The JBI Transfer Science Scholarly Framework can be divided into three areas of inquiry: education, systems integration and active dissemination. Education involves a wide range of programs delivered both face-to-face and online to a variety of health-related professions. Systems integration refers to both online and offline sets of procedures or mechanisms that are used within healthcare that need to be integrated and compatible with the ability to be populated with evidence-based recommendations. Active dissemination is largely a communicative function aimed at spreading knowledge on a large scale within and across geographic locations, practice settings and other networks to end users. Results: This is a new area of scientific focus for the JBI. The three pillars outlined above are essential for ensuring tools and resources are meaningful in clinical and health management/policy contexts in order to advance the access to and uptake of evidence.